ESTIMULAÇÃO PRECOCE: O CASO DE UMA CRIANÇA COM SEQUÊNCIA DE PIERRE ROBIN - Martins, Rosely Vieira dos Santos (2020)
This study analyzes the process of early stimulation of a child with Special Educational Needs (SEN), due to Pierre Robin Sequence (PRS), attended by a private-philanthropic institution of Special Education, relating the family and specialized contexts. The qualitative approach was used, with descriptive analyzes, using bibliographic and field research for data collection as technical procedures, through a case study. From the analyzes, it was possible to notice that, since the arrival of the child with PRS at the institution, in 2015, until the year of the research, in 2018, there was progress in its development, also made possible by the mother's participation, despite the difficulties of work of the last teacher, who reported a lack of experience with this type of specialized pedagogical intervention. Thus, the need for institutional support is defended so that there is no rupture between the practices developed by the teachers, in order to guarantee the integral development of the child and articulation between all agents and services involved with early stimulation.